Indira Awaas Yojana A Quick Study 1992-93 - Planning Commission (Planning Commission, 1992)
At the instance of the Planning Commission, the Programme Evaluation Organisation (PEO) undertook a Quick Study of the Indira Awaas Yojana (IAY) with a view to ascertain the processes involved in selection of households and construction of houses including agencies responsible; assess the quality of houses constructed; the extent of their occupation and the level of satisfaction of the allottees. During 1985-1992, taking all the States and Union Territories together, 1.06 million houses were constructed; at a total cost of Rs. 1139.75 crores. Of these; 97.5 per cent were constructed in 14 States. Further, about 50 per cent of the houses were constructed only in 3 States of Tamil Nadu, Uttar Pradesh, and Bihar, and Tamil Nadu alone accounted for 21 per cent. The Study was conducted in these 14 States covering 14 Districts, 28 Blocks, and 56 Villages. The PEO field teams studied the Yojana for about a week in the selected villages and interviewed 1195 out of 1224 selected households. The reference period of the Study was from 1985-86 to 1991-92.
Programme Evaluation Organisation Planning Commission (Government of India) New Delhi